Verbascum seydisehirense (Scrophulariaceae), a new species from Konya, Central Turkey - Ulukuş, Deni̇z; Tugay, Osman; Sağlam, Coşkun (Phytotaxa, 2020)
Verbascum seydisehirense (Scrophulariaceae), endemic to the Konya region of Central Anatolia, is described as new species based on the plant’s morphological features. The new species is morphologically similar to Verbascum phrygium, but it differs from it for basal leaf shape, calyx size, corolla size, corolla indumentum and glands, and capsule shape and size. In this study, a detailed description, illustration, distribution map, conservation status and ecology of the new species are provided. Additionally, the study looks in detail at pollen grains and seed coat ornamentation of Verbascum seydisehirense and includes SEM micrographs.